CAPTURED MALAISE IN CONTEMPORARY CAPITALISM - de Oliveira Neto, Francisco José (Seven Editora, 2026)
Since Freud, the concept of malaise in civilization has designated the structural tension between desire, social bonds, and instinctual renunciation. In contemporary society, this tension is intensified by neoliberal rationality and the logic of late capitalism, which reconfigure both forms of suffering and modes of substitutive satisfaction. Although the literature widely acknowledges the commodification of psychic suffering, the subjective dynamics involved in contemporary practices of affective substitution—such as bonds with reborn babies and the parentalization of companion animals—remain underexplored. This study aims to analyze, in light of psychoanalysis and critical theory, how such practices operate as defensive solutions to malaise, articulating fantasy, fetishism, and narcissism within the logic of consumption. This is a qualitative study of a theoretical-analytical nature, guided by the hermeneutic-critical method and based on a critical review of psychoanalytic and philosophical literature, with emphasis on classical and contemporary authors such as Freud, Winnicott, Adorno, Horkheimer, Benjamin, Rosa, and Byung-Chul Han, in dialogue with recent international scholarship. It is argued that the affective substitutions analyzed function as fetishistic and narcissistic formations that suspend alterity, neutralize the experience of loss, and offer an illusory relief from psychic suffering. At the same time, such practices are captured and amplified by the market, which transforms subjective impasses into consumer niches. It is concluded that these configurations, far from promoting symbolic elaboration, tend to freeze suffering, reinforcing repetitive circuits of satisfaction and frustration. The study contributes to the fields of clinical practice, education, and the humanities by highlighting the need for symbolic and collective dispositifs that enable the elaboration of mourning and the reestablishment of bonds with alterity. DOI: https://doi.org/10.56238/sevened2026.008-110